2007
DOI: 10.1177/159101990701300201
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Rupture Mechanism of Partially Thrombosed Aneurysms

Abstract: Within the group of giant and large aneurysms the subgroup of the so-called “partially thrombosed” aneurysms can be differentiated according to clinical and neuroimaging findings. The present study was carried out to determine the site of bleeding of these aneurysms and what implications concerning their pathomechanism can be drawn from these findings. Twenty patients aged two to 77 (mean 44) years who exhibited a partially thrombosed aneurysm that had recently bled were included. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 20 publications
(37 reference statements)
2
68
1
2
Order By: Relevance
“…Some propose that the vasa vasorum of the aneurysmal wall play a crucial role in the development and growth of aneurysms with intraluminal thrombus by proliferation, inflammation, and rupture. [25][26][27] These authors suggest that these aneurysms should be treated by targeting the outer vessel wall and not the aneurysmal lumen. Our study does not confirm this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Some propose that the vasa vasorum of the aneurysmal wall play a crucial role in the development and growth of aneurysms with intraluminal thrombus by proliferation, inflammation, and rupture. [25][26][27] These authors suggest that these aneurysms should be treated by targeting the outer vessel wall and not the aneurysmal lumen. Our study does not confirm this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also demonstrated that most late mortality was due to continuous growth of some basilar tip aneurysms despite adequate first-time occlusion with coils and additional coiling when possible. 22,23 Why this phenomenon occurs in some aneurysms remains unclear. We were unable to identify risk factors for this infrequent event.…”
Section: Discussionmentioning
confidence: 99%
“…10 Subsequent MRI studies revealed repeated episodes of intramural hematoma, gradually evolving into a lesion with imaging characteristics as previously described in PTAs, including T1 hyperintensity indicating methemoglobin and an onion skin-like layering of hematomas of varying ages. 1,6,17 Growth of the aneurysm was revealed to occur due to the repeated hemorrhages that were distant from the perfused lumen, with stable imaging characteristics of the focally dilated lumen.…”
Section: Operation and Postoperative Coursementioning
confidence: 99%